2011
DOI: 10.1362/147539211x589546
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a moderator of temperamental causes of impulse buying tendency

Abstract: Stern, 1962). The behavioural approach to consumer decision-making treats the impulse buying tendency as an individual trait, which in certain circumstances can lead to an act of impulse buying (e.g. AbstractThe behavioural approach to consumer decision-making focuses on impulse buying tendency as an individual trait that (in certain circumstances) leads to an act of impulse buying. Many authors believe that this trait is related to general impulsiveness as a temperamental factor. However, there is no precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 56 publications
2
18
0
10
Order By: Relevance
“…According to Gąsiorowska (2011), three groups of factors stimulating impulsive buying can be distinguished. The first group consists of individual characteristics that influence the impulse buying tendency; the second group consists of individual and situational factors that trigger impulses while shopping; and the third group consists of moderating factors that restrain or stimulate impulse buying behavior.…”
Section: Situational Factors and Impulse Buyingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Gąsiorowska (2011), three groups of factors stimulating impulsive buying can be distinguished. The first group consists of individual characteristics that influence the impulse buying tendency; the second group consists of individual and situational factors that trigger impulses while shopping; and the third group consists of moderating factors that restrain or stimulate impulse buying behavior.…”
Section: Situational Factors and Impulse Buyingmentioning
confidence: 99%
“…Mihić and Kursan (2010a) find that there are no statistically significant differences between males and females regarding their impulse buying behavior. Gąsiorowska (2011) finds that males and females differ in terms of psychological drivers of impulse buying. As most of the performed studies in this field showed that gender affects impulsive purchasing, Hypothesis 1 has been formulated: H1: Impulsive buying behavior varies according to gender.…”
Section: Demographic and Socioeconomic Factors And Impulse Buyingmentioning
confidence: 99%
“…The behaviour of impulse buying is a result of the impact of marketing-mix strategy and the personal attributes and traits of the consumer (Gąsiorowska, 2011). With regard to the fi ve personality traits of consumers discussed above; Neuroticism is positively correlated with a risk-aversive behaviour because it is linked to the feeling of anxiety, while Openness to Experience positively predicts impulsive behaviour (Dowd & McElroy, 2007).…”
Section: Impulsive Careless Consumermentioning
confidence: 99%
“…Segundo Gąsiorowska (2011), o sexo de pertença exerce um papel moderador na relação entre as diferenças individuais e a tendência à compra por impulso. Um estudo realizado por Silvera, Lavack e Kropp (2008) mostrou que as mulheres tendem a comprar mais por impulso do que os homens, corroborando outros estudos que obtiveram resultados semelhantes (Alagöz & Ekici, 2011;.…”
Section: Variáveis Sociodemográficasunclassified